Autoantibodies in Diabetes Mellitus - Herawati, Eka; Susanto, Ardian; Sihombing, Christina Noventy (Molecular and Cellular Biomedical Sciences, 2017)
Based on American Diabetes Association (ADA), diabetes can be classified into the following general categories: type 1 diabetes (T1D), type 2 diabetes (T2D), gestational diabetes mellitus (GDM) and specific types of diabetes due to other cause. Obesity is by far the main underlying factor causing T2D and its pathological potential lies in obesity-associated insulin resistance, activation of innate immunity and chronic low-grade inflammation. When tissue inflammation induced, tissue destruction occurs, self antigens, which are generally not accessible to T cells, can be released from the affected tissues and promote autoimmune activation. The 4 major autoantibodies are islet-cell cytoplasmic autoantibodies (ICA), glutamid acid decarboxylase antibody (GADA), islet antigen-2 antibody (IA-2A) and insulin autoantibodies (IAA). In addition, ZnT8A has recently been found to predict T1D. ZnT8 is contained in the islets of Langerhans, with the highest expression is in Î² cells of the pancreas. ZnT8A measurements simultaneously with GADA, IA-2A and IAA achieve rates of 98% detection for onset level of autoimmune diabetes. Presence of antibodies in T2D also shows the potential serious complications compared with T2D without antibodies. The combination of GADA, IA-2A and ZnT8A can be suggested as the most powerful and cost-effective diagnostic approach in patients with T1D.Keywords: autoantibody, autoimmune, diabetes mellitus, ICA, GADA, IA-2A, IAA, ZnT8A